2006
DOI: 10.1590/s0103-97332006000300031
|View full text |Cite
|
Sign up to set email alerts
|

Infinite potential barrier and hydrostatic pressure effects on impurity-related optical absorption spectra in GaAs double quantum wells

Abstract: Using the effective-mass approximation and the variational method, we have calculated the effects of hydrostatic pressure on the donor-and acceptor-related optical absorption spectra in symmetrical GaAs double quantum well structures. A central finite potential barrier and two infinite external barriers constitute the profile of the potential barrier considered for the wells. Our results are presented as a function of the well and barrier widths and hydrostatic pressure. For the pressure dependence we consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Finally, the results presented above are generally in good agreement with those of several authors concerning different LDS-shapes based on different semiconductor materials, GaAsGa 0.7 Al0 0.3 As symmetric double QWs [16], InGaN QWs [8], GaN [17] CQWs and InGaN CQDs [18]. However, some discrepancies remain due to the wave-function, the analytical method and structure-shape used in each paper.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, the results presented above are generally in good agreement with those of several authors concerning different LDS-shapes based on different semiconductor materials, GaAsGa 0.7 Al0 0.3 As symmetric double QWs [16], InGaN QWs [8], GaN [17] CQWs and InGaN CQDs [18]. However, some discrepancies remain due to the wave-function, the analytical method and structure-shape used in each paper.…”
Section: Resultssupporting
confidence: 86%
“…It is also found that the binding energy is not symmetric with respect to z 0 ¼ 0. In the same sense, Raigoza et al [16] have shown that the binding energy of infinite potential barrier GaAs-Ga 0.7 Al 0.3 As symmetric double QWs, with L w ¼ 7:5 nm and L b ¼ 3 nm, has two structures for all hydrostatic pressure values (Fig. 2 [16]).…”
Section: Resultsmentioning
confidence: 90%
“…The δ − doping semiconductors' quantum wells are very important for designing various optoelectronic devices based on optical intersubband transitions. Many research works have been developed theoretically and experimentally to investigate the behavior of optical properties in quantum wells, quantum wires and quantum dots [13][14][15][16][17][18][19][20][21][22][23][24][25]. Majority of provided results indicate that various factors such as δ − doping concentration, temperature, applied external electric field and hydrostatic pressure affect the electronic and optical properties of these semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the silicon layer creates a triangular-shaped quantum well which would affect the spatial spread of the wave functions and furnish further confinement to the carriers [32,33]. Various research works have explored, both experimentally and theoretically, the impact of δ-doping on the behavior of the TOAC in semiconductor quantum nanostructures [34][35][36][37][38][39][40][41]. For instance, Gaggero-Sager et al studied the effects of temperature on the energy levels in a single doped QW [42], whereas Dhafer et al showed the importance of an inserted δ-InGaAs layer in a single Al x Ga y In 1−x−y As QW.…”
Section: Introductionmentioning
confidence: 99%